Cost Growth and Stock Returns - Huang, Dashan (Institutional Knowledge at Singapore Management University, 2014)
In this paper, we examine the valuation implications of cost behavior, and find that firms with high growth rate in operating costs generate substantially lower future stock returns than those with low cost growth. A spread portfolio of long stocks with low cost growth and short stocks with high cost growth earns an average abnormal return of 12% per year. This strategy is robust over time, across market capitalization, and to control for alternative anomalies and risks. Cost growth is strongly associated with deterioration in a firm’s future profitability, which investors appear failing to incorporate into valuation. In addition, the negative cost growth-return relation is stronger among firms with lower investor attention, higher valuation uncertainty, and higher transaction costs, suggesting that mispricing plays an important role in explaining the cost growth effect.